Risk of adverse pregnancy outcomes in women with periodontal disease and the effectiveness of interventions in decreasing this risk: protocol for systematic overview of systematic reviews. Issue 1 (December 2016) - Vanterpool, Sizzle; Tomsin, Kathleen; Reyes, Leticia; Zimmermann, Luc; Kramer, Boris; Been, Jasper
Abstract Background Periodontal disease is an inflammatory disease of the tissues supporting the teeth. Women who have periodontal disease while pregnant may be at risk of adverse pregnancy outcomes. Although the association between periodontal disease and adverse pregnancy outcomes has been addressed in a considerable number of systematic reviews and meta-analyses, there are important differences in the conclusions of these reviews. Systematic reviews assessing the effectivity of various therapeutic interventions to treat periodontal disease during pregnancy to try and reduce adverse pregnancy outcomes have also arrived at different conclusions. We aim to provide a systematic overview of systematic reviews comparing the frequency of adverse pregnancy outcomes between women with and without periodontal disease and/or evaluating the effect of preventive and therapeutic interventions for periodontal disease before or during pregnancy on adverse pregnancy outcomes. Methods We will include systematic reviews reporting on studies comparing adverse pregnancy outcomes: (i) between women with or without periodontal disease before (<6 months) or during pregnancy and/or (ii) according to preventive or therapeutic interventions for periodontal disease. Eligible interventions include (combinations of) the following: oral hygiene education, use of antibiotics, subgingival scaling, and root planing. For preventive and/or therapeutic reviews, the following comparisons will be considered: no intervention, a placebo intervention, or an alternative intervention. Our primary adverse pregnancy outcomes of interests are maternal mortality, preterm delivery, and perinatal mortality. Two reviewers will independently identify eligible published and unpublished systematic reviews from six electronic databases and using hand searching of reference lists and citations. Data items extracted from included systematic reviews are based on the Cochrane Effective Practice and Organization of Care checklist and the preferred reporting items for systematic review and meta-analysis (PRISMA) statement. In our narrative data synthesis, we will consider risk of bias of individual reviews, focusing mainly on the conclusions of the highest quality reviews using the assessment of multiple systematic reviews (AMSTAR) checklist. Disagreements during search, selection, data extraction, and risk of bias assessment will be resolved through discussion and/or consultation of a third reviewer. Systematic review registration PROSPEROCRD42015030132